2023
DOI: 10.1039/d2gc03534k
|View full text |Cite
|
Sign up to set email alerts
|

Endowing cells with unnatural photocatalytic ability for sustainable chemicals production by bionic minerals-triggering

Abstract: Photobiological chemicals production is of great importance for solar energy storage and clean fuel generation. One rising strategy for the solar fuels production is to enhance the non-photosynthetic cells’ original...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The remaining fourth coordination bond can bind to H 2 O, allowing the activated water molecules to accept electrons from the nCdS and generate H 2 . 557 In another study, Ding et al designed multiple core-shell structured quantum dots (QDs) encapsulated in zinc sulfide (ZnS) shell and introduced the target enzymes (hydrogenase and nitrogen-fixing enzymes, with expression of a histidine tag (His-tag)) into microbial cells. The ZnS shell allowed the QDs to bind to target enzymes specifically, and the photogenerated electrons from QDs were directly transferred to the enzymes upon illumination, which effectively improved the light-driven H 2 production and N 2 fixation.…”
Section: Enhancing Inward Electron Transfer By Materials-cells Integr...mentioning
confidence: 99%
“…The remaining fourth coordination bond can bind to H 2 O, allowing the activated water molecules to accept electrons from the nCdS and generate H 2 . 557 In another study, Ding et al designed multiple core-shell structured quantum dots (QDs) encapsulated in zinc sulfide (ZnS) shell and introduced the target enzymes (hydrogenase and nitrogen-fixing enzymes, with expression of a histidine tag (His-tag)) into microbial cells. The ZnS shell allowed the QDs to bind to target enzymes specifically, and the photogenerated electrons from QDs were directly transferred to the enzymes upon illumination, which effectively improved the light-driven H 2 production and N 2 fixation.…”
Section: Enhancing Inward Electron Transfer By Materials-cells Integr...mentioning
confidence: 99%
“…17 It has also been used in the production of polyhydroxybutyrate (bioplastic precursor) 18 and generates green energy via producing hydrogen. 19 Similarly, solar-driven biohydrogen production has been achieved on the biohybrids of CdS-E. coli 3 and CdS-S. cerevisiae, 20 and solar-enhanced PHB production has been observed from the biohybrid of g-C 3 N 4 -R. eutropha. 21 In comparison, photoheterotrophic R. rubrum is capable of utilizing relatively cheap and low-energy substrates (e.g., small-molecular organic acids), a property that makes the chemical production more energy efficient and cost-effective than traditional sugar-based biomanufacturing platforms (e.g., glucose for E. coli and S. cerevisiae, fructose for R. eutropha).…”
Section: Introductionmentioning
confidence: 99%
“…17 It has also been used in the production of polyhydroxybutyrate (bioplastic precursor) 18 and generates green energy via producing hydrogen. 19 Similarly, solar-driven biohydrogen production has been achieved on the biohybrids of CdS– E. coli 3 and CdS– S. cerevisiae , 20 and solar-enhanced PHB production has been observed from the biohybrid of g-C 3 N 4 – R. eutropha. 21 In comparison, photoheterotrophic R. rubrum is capable of utilizing relatively cheap and low-energy substrates ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…14 We previously reported that the fungus Saccharomyces cerevisiae was altered to efficiently engage in unnatural solar-to-hydrogen production via modifying the structure of alcohol dehydrogenases (ADHs) using intracellular CdS nanodots generated in situ. 15 We also reported that nanohydroxyapatite-hybrid hemoglobin synthesized in situ in red blood cells enabled efficient electrocatalyzation of the oxygen reduction reaction (ORR), which is distinct from their natural oxygen-carrying function. 16 Although a few studies have been conducted, the strategies utilized primarily depend on an empirical trial-and-error approach.…”
Section: Introductionmentioning
confidence: 99%